Scholarly Influence in Criminology and Criminal Justice of China - Zhang, Yan (Asian journal of criminology, 2017)
Scholarly influence in criminology and criminal justice (CCJ) is not a new topic. However, in terms of international scholarly influence in Chinese criminology, there still exists no relevant literature, though emphasis on studying China has been increasingly recognized by the international criminological academy. The current study conducts a comprehensive analysis of 191 CCJ articles on China from 20 mainstream CCJ journals and locates those who have done work on Chinese criminology. By productivity and citation analysis, we obtain several rankings of the scholarly influence in Chinese criminology. The most prolific individual identified by the current study is Jianhong Liu; the most productive institution is the City University of Hong Kong; the most-cited scholar is Steven Messner, and the most-cited work is Policing and Punishment in China: From Patriarchy to ‘The People’ by Michael Dutton. Though the current study focuses on Chinese criminology, few local mainland Chinese scholars and publications in Chinese are among the dominant contributions.